Adaptation and Validation of a Scale of Self-Regulation of Learning in Mathematical Problem Solving - Landa, Josune (2024)
[Objective] This work aims to adapt and validate a scale that measures the level of self-regulation in mathematical problem-solving contexts of teachers in initial training in primary education. [Methodology] For sample selection, non-probabilistic convenience or incidental sampling was used. A total of 269 first-year primary education undergraduate degree students at the University of the Basque Country (UPV/EHU) in the 2020–2021 academic year participated in the validation process of the adapted scale. The type of research conducted is descriptive. Data were analyzed using the SPSS statistical software. [Results] The Cronbach's alpha coefficient value of 0.884 revealed a consistent internal reliability. Likewise, to test the factor structure of the scale, an exploratory factor analysis was conducted, obtaining a Kaiser-Meyer-Olkin (KMO) index of 0.836 > 0.7 and a p= 0.000<0.05 in the Bartlett test of sphericity. It also indicated a seven-factor structure: students' perceptions of their ability and how these perceptions influence self-regulation of the resolution process; ethics, problem-solving and personal growth; attitude towards the statement; negative self-efficacy beliefs; external causal attribution; problem-solving methods; and the social environment. [Conclusions] The latent structure provided by the exploratory factor analysis agrees with the classification of items established a priori and allows for the orientation of the confirmatory factor analysis that provides continuity to the research.